A internalização dos princípios da norma ISO 26000: o caso da Petrobrás - Silva, Arthur William Pereira da (2014)
The ISO 26000 standard has been contributing to the development of RSE, but still retains the generic nature characteristic of previous approaches and the absence of indicators. Within this context, a guiding question is made from this research: does the lack of indicators for the rule ISO 26000 implicates with the assessment and consequently with the internalization of the socially responsible behavior by the organizations? As the main objective the research proposes: to analyze PETROBRAS sustainability report to identify how the principle of the ISO 26000 standard are internalized. As a secondary objective, the research seeks to: check whether the principle of the ISO 26000 keeps the generic form of the classical approaches to corporate social responsibility; Find out how many companies operating in exploration and production of oil and natural gas sector in Brazil implemented the ISO 26000 standard; Check for any contradictions between PETROBRAS talks over social responsibility and its actions. This research was developed in two stages, one was exploratory and the other explanatory. The method of research used was the case studied, and the company studied was Petróleo Brasileiro S/A PETROBRAS. The approach chosen for data collection was a documentary research. The research results showed that: The principle of ISO 26000 keeps the generic form of the classical approaches to corporate social responsibility; of all the 97 organizations that operate in the exploration and production of oil and natural gas segment in Brazil, only PETROBRAS states that it has implemented the ISO 26000 standard; There are contradictions between PETROBRAS talks on social responsibility and some of its actions, and finally, the generality and lack of indicators to measure the level of adequacy of the actions taken by the company and proposed actions by the principle of ISO 26000, compromises the assessment of socially responsible behavior by the organizations.